Carlos Seré on how Africa can adapt to climate change - International Livestock Research Institute (International Livestock Research Institute, 2010)
The International Livestock Research Institute (ILRI) says Africa must learn to adapt to shorter growing seasons following findings of a new study that warns of the potential problems Africa faces from rising temperatures. The report, which was released at the U.N. Climate Change Conference in Cancun, Mexico, considers what might happen if global temperatures increased by four degrees. ILRI's Director-General Carlos Seré is interviewed by the Voice of America.